Peningkatan Minat Belajar Matematika Siswa melalui Strategi Pembelajaran Active Knowledge Sharing di Kelas VIII SMPN 03 2x11 Kayutanam Tahun Ajaran 2021/2022 - Afdhal Juli Hendri; Rusdi Rusdi; Aniswita Aniswita; Tasnim Rahmat (Departement of Mathematics Education, 2023)
This study aims to determine the increase in interest in learning mathematics for class VIII students of SMPN 03 2x11 Kayutanam through active knowledge sharing learning strategies. This type of research is pre-experimental with a one group pretest posttest research design. The population of this study were all students of class VIII SMPN 03 2x11 Kayutanam. The sampling technique was carried out by means of random sampling, and assigned class VIII A as the sample class. The instruments used in this study were pretest and posttest questionnaires for students' learning interest with an active knowledge sharing strategy. The data analysis technique used to test the hypothesis is the paired sample t test. Based on the results of the data analysis obtained from the average student pretest questionnaire results was 49.125 while the average student posttest questionnaire results were 70.667. Based on the calculation results of the paired sample t test at the significance level ???? = 0.05, the tcount = 8.749 and ttable = 1.714. Based on the results of the calculation th > tt, it means rejecting H0 and accepting H1, meaning that there are differences in students' interest in learning mathematics after using the active knowledge sharing strategy in class VIII students of SMPN 03 2x11 Kayutanam. So that in this study it can be concluded that there is an increase in students' interest in learning mathematics with active knowledge sharing learning strategies in class VIII SMPN 03 2x11 Kayutanam.